Optimizing functional accuracy of TMS in cognitive studies: a comparison of methods. - Sack, A; Cohen Kadosh, R; Schuhmann, T; Moerel, M; Walsh, V; Goebel, R (2009)
Transcranial magnetic stimulation (TMS) is a tool for inducing transient disruptions of neural activity noninvasively in conscious human volunteers. In recent years, the investigative domain of TMS has expanded and now encompasses causal structure-function relationships across the whole gamut of cognitive functions and associated cortical brain regions. Consequently, the importance of how to determine the target stimulation site has increased and a number of alternative methods have emerged. Comparison across studies is precluded because different studies necessarily use different tasks, sites, TMS conditions, and have different goals. Here, therefore, we systematically compare four commonly used TMS coil positioning approaches by using them to induce behavioral change in a single cognitive study. Specifically, we investigated the behavioral impact of right parietal TMS during a number comparison task, while basing TMS localization either on (i) individual fMRI-guided TMS neuronavigation, (ii) individual MRI-guided TMS neuronavigation, (iii) group functional Talairach coordinates, or (iv) 10-20 EEG position P4. We quantified the exact behavioral effects induced by TMS using each approach, calculated the standardized experimental effect sizes, and conducted a statistical power analysis in order to calculate the optimal sample size required to reveal statistical significance. Our findings revealed a systematic difference between the four approaches, with the individual fMRI-guided TMS neuronavigation yielding the strongest and the P4 stimulation approach yielding the smallest behavioral effect size. Accordingly, power analyses revealed that although in the fMRI-guided neuronavigation approach five participants were sufficient to reveal a significant behavioral effect, the number of necessary participants increased to n = 9 when employing MRI-guided neuronavigation, to n = 13 in case of TMS based on group Talairach coordinates, and to n = 47 when applying TMS over P4. We discuss these graded effect size differences in light of the revealed interindividual variances in the actual target stimulation site within and between approaches.